Common virulence factors between Histoplasma and Paracoccidioides: Recognition of Hsp60 and Enolase by CR3 and plasmin receptors in host cells (2024)
ABSTRACT: Over the last two decades, the incidence of Invasive Fungal Infections (IFIs) globally has risen, posing a considerable challenge despite available antifungal therapies. Addressing this, the World Health Organization (WHO) prioritized research on specific fungi, notably Histoplasma spp. and Paracoccidioides spp. These dimorphic fungi have a mycelial life cycle in soil and a yeast phase associated with tissues of mammalian hosts. Inhalation of conidia and mycelial fragments initiates the infection, crucially transforming into the yeast form within the host, influenced by factors like temperature, host immunity, and hormonal status. Survival and multiplication within alveolar macrophages are crucial for disease progression, where innate immune responses play a pivotal role in overcoming physical barriers. The transition to pathogenic yeast, triggered by increased temperature, involves yeast phase-specific gene expression, closely linked to infection establishment and pathogenicity. Cell adhesion mechanisms during host-pathogen interactions are intricately linked to fungal virulence, which is critical for tissue colonization and disease development. Yeast replication within macrophages leads to their rupture, aiding pathogen dissemination. Immune cells, especially macrophages, dendritic cells, and neutrophils, are key players during infection control, with macrophages crucial for defense, tissue integrity, and pathogen elimination. Recognition of common virulence molecules such as heat- shock protein-60 (Hsp60) and enolase by pattern recognition receptors (PRRs), mainly via the complement receptor 3 (CR3) and plasmin receptor pathways, respectively, could be pivotal in host-pathogen interactions for Histoplasma spp. and Paracoccidioides spp., influencing adhesion, phagocytosis, and inflammatory regulation. This review provides a comprehensive overview of the dynamic of these two IFIs between host and pathogen. Further research into these fungi's virulence factors promises insights into pathogenic mechanisms, potentially guiding the development of effective treatment strategies.